2015
DOI: 10.1002/jssc.201400946
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive analysis of multiple bioactive constituents in tripterygium glycosides tablets using liquid chromatography coupled with time‐of‐flight mass spectrometry

Abstract: A simultaneous determination method based on liquid chromatography coupled with time-of-flight mass spectrometry was developed for the analysis of 11 bioactive constituents in tripterygium glycosides tablets, an immune and inflammatory prescription used in China. The analysis was fully optimized on a 1.8 μm particle size C18 column with linear gradient elution, permitting good separation of the 11 analytes and two internal standards in 21 min. The quantitation of each target constituent was carried out using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…4B). This annotation also was consistent with the elution order and fragmentation patterns of sesquiterpene alkaloids reported previously for reverse-phase HPLC-MS and MS/MS (molecular ion as base peak, with abundant fragments at m/z 206 and 856; Zeng et al, 2013;Cai et al, 2015;Su et al, 2015;Luo et al, 2016). No NMR data were acquired in this study.…”
Section: ])supporting
confidence: 92%
See 1 more Smart Citation
“…4B). This annotation also was consistent with the elution order and fragmentation patterns of sesquiterpene alkaloids reported previously for reverse-phase HPLC-MS and MS/MS (molecular ion as base peak, with abundant fragments at m/z 206 and 856; Zeng et al, 2013;Cai et al, 2015;Su et al, 2015;Luo et al, 2016). No NMR data were acquired in this study.…”
Section: ])supporting
confidence: 92%
“…Previous studies that used reversephase chromatography with Tripterygium root extracts consistently listed wilfortrine as the earliest eluting abundant peak associated with this formula (Zeng et al, 2013;Cai et al, 2015;Su et al, 2015;Luo et al, 2016). The MS/MS fragmentation patterns we obtained at a collision energy of 30 eV were almost identical to those reported for wilfortrine when recorded at 25 eV (major product ion at m/z 846; Cai et al, 2015).…”
Section: Development Of Spectral Libraries To Expedite the Identificasupporting
confidence: 75%
“…Previous studies reported that TGT acts as anti-inflammation, inhibiting cell immunity and humoral immunity, dispelling wind, detoxification, eliminating dampness, subsidence of swelling, and dredging collaterals [5,6]. Hundreds of RCTs have shown that TGT was widely used to treat AS in China [7], but its efficacy has not been reviewed systematically.…”
Section: Discussionmentioning
confidence: 99%
“…TGT is capable of anti-inflammation, inhibiting cell immunity and humoral immunity, dispelling wind, detoxification, eliminating dampness, subsidence of swelling, and dredging collaterals [5,6]. TGT (10 mg per tablet) should be Hong Li and Feng Guo are both considered as co-first authors.…”
Section: Introductionmentioning
confidence: 99%
“…Tripterygium wilfordii is a plant of the family Celastraceae. It has been shown that Tripterygium wilfordii has pharmacological properties such as anti-inflammatory, immunity regulation, anti-tumor, and reproduction suppression effects, so it is widely applied for treating rheumatoid arthritis, glomerular nephritis, lupus erythematosus, and many autoimmune and skin diseases with significant effects (Wang et al, 2015;Su et al, 2015). In this study, the clinical effects of T. wilfordii on CGN were observed, aiming to further investigate its mechanism of action.…”
Section: Introductionmentioning
confidence: 96%